2008
DOI: 10.2308/jata.2008.30.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Taxes and Asset Prices: The Case of Thoroughbreds

Abstract: This study examines the thoroughbred auction market in order to assess the effect of taxes on asset prices. Yearlings purchased from 2002 to 2004 are eligible for bonus depreciation, and the price of the yearlings is predicted to be bid up during this period. The research design employs pricing models that have been published in economics and agri-business academic journals. These models control for such factors as yearling lineage, gender, and month foaled. Thoroughbreds are sold annually, and much of the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…A third possibility is that the price of capital goods increased in response to bonus depreciation, which would have had the effect of decreasing capital spending at the same time that bonus depreciation's tax benefits had the effect of increasing it (Davis and Swenson, 1993;Key, 2008). The data we use does not provide the price of firms' capital goods, so we are unable to assess this possibility.…”
Section: Discussion Of Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…A third possibility is that the price of capital goods increased in response to bonus depreciation, which would have had the effect of decreasing capital spending at the same time that bonus depreciation's tax benefits had the effect of increasing it (Davis and Swenson, 1993;Key, 2008). The data we use does not provide the price of firms' capital goods, so we are unable to assess this possibility.…”
Section: Discussion Of Resultsmentioning
confidence: 94%
“…As is discussed below, our study differs from these studies by including a broader set of control variables, which are based on the user cost of capital model and prior research on capital spending. Key (2008) examined the price of yearling and broodmare horses during bonus depreciation's availability versus the year before and the year after its availability. She found that the price of yearlings, which qualified for bonus depreciation, was higher during its availability, but the price of broodmares, which did not qualify for bonus depreciation, was insignificantly smaller.…”
Section: Relevant Empirical Studies On Bonus Depreciationmentioning
confidence: 99%
“…quarterly and annual data of shipments in the general aviation aircraft industry from 1987 to 2005 and document a significant negative relation between bonus depreciation and the annual ratio of piston to (more expensive) turbine general aviation aircraft shipments. The findings are consistent with their expectations that the impact of bonus depreciation should be strongest for expensive aircraft Key, 2008,. examines market prices in the equine industry from 2001 to 2005.…”
supporting
confidence: 86%
“…The two main policy instruments were the Development Area Law (DAL) and the Investment Subsidy Law (ISL). Like bonus depreciation policies in the U.S. after 9/11 as well as after the economic crisis of 2008-2009(Zwick and Mahon, 2014, DAL granted generous bonus depreciation for tax purposes of up to 50% of the investment. The second subsidy scheme, ISL, was launched in 1991 and ran out at the end of 2013.…”
Section: Introductionmentioning
confidence: 99%
“…While there is research suggesting a positive effect of bonus depreciation regulations in the U.S. (Billings, Musazi, and Houston, 2008;Key, 2008;Edgerton, 2012;Park, 2012;Zwick and Mahon, 2014) and the Netherlands (Wielhouwer and Wiersma, 2013), the evidence is not fully conclusive. Using a difference-in-differences estimation strategy, Cohen and Cummins (2006) are not able to provide comprehensive empirical results.…”
Section: Introductionmentioning
confidence: 99%